The Effectiveness of Choice Theory Education with a STEM-Based Approach on Students’ Self-Efficacy and Creativity - Seyfi, Khadijeh; Sanagouye Moharer, Gholamreza; Shirazi, Mahmoud (Iranian Journal of Neurodevelopmental Disorders, 2024)
Objective: This study aimed to evaluate the effectiveness of STEM-based choice theory education on enhancing self-efficacy and creativity among female high school students. Methods and Materials: The research employed a quasi-experimental design with a pretest-posttest control group structure. A total of 30 female high school students from District 5 of Tehran were selected through convenience sampling and randomly assigned to experimental (n=15) and control (n=15) groups. The experimental group participated in a 10-session intervention involving STEM-based choice theory education, while the control group received no intervention. Self-efficacy and creativity were assessed using validated questionnaires before and after the intervention. Data were analyzed using multivariate covariance analysis (MANCOVA) to determine the intervention’s impact. Findings: The results indicated significant improvements in both self-efficacy and creativity in the experimental group compared to the control group. For self-efficacy, the intervention explained 89.7% of the variance (F(1, 24) = 208.425, p < 0.001, η² = 0.897), while for creativity, it accounted for 93.1% of the variance (F(1, 24) = 324.466, p < 0.001, η² = 0.931). These findings suggest that STEM-based choice theory education effectively fosters both self-belief and innovative thinking in students. Conclusion: STEM-based choice theory education is a highly effective approach to enhancing self-efficacy and creativity among high school students. By addressing cognitive and emotional dimensions of learning, this intervention offers a robust framework for empowering students and preparing them for complex problem-solving and innovation. The results highlight the importance of integrating psychological theories and interdisciplinary education into school curricula to foster comprehensive student development.